Evolución de la televisión ecuatoriana frente a las plataformas Streaming - Mosquera Chang, Gardenia Genoveva (2022)
The present case study focuses on analyzing the evolution of Ecuadorian television channels, compared to streaming platforms, in order to know how traditional media have been submerged in digital platforms, because new audiences currently opt for the consumption of content on various digital platforms. To obtain the results in this research, a quantitative and qualitative methodology was used, using survey and observation techniques. The observation was carried out, through content analysis, to the traditional television medium in comparison with the live streaming platforms; while the survey was applied to a number of 20 people, who are part of the main social media using streaming platforms and the general public in the city of Babahoyo, the questionnaire consists of 10 closed multiple-choice questions, in order to obtain precise and concrete information. The results showed that the habit of consuming information in real time is mainly linked to the great evolution that digital platforms have had, thanks to improvements in internet access coverage; also to the multiple content changes, the immediacy and access offered by the aforementioned platforms to stay informed or entertained. Therefore, based on these findings in this study it is recommended to consider streaming platforms, for the creation of journalistic content, in the present and future generation of journalists, since communication requires constant adaptation, to remain current according to the audiences.